Mentors' perceptions and experiences of supporting student nurses in practice. Issue 4 (23rd August 2013) - McIntosh, Annette; Gidman, Janice; Smith, Debra
<x xml:space="preserve">Abstract</x> This paper reports on a funded project that explored the perceptions and experiences of mentors regarding student nurse support in practice. The study employed a mixed‐method approach, using questionnaires and focus groups with mentors from one acute Trust and one community Trust. The findings highlighted the multifaceted nature of student learning in practice, with mentors reporting that clinical skills, adjustment to the placement and integrating into the team were the aspects students needed most support with. Mentors were aware of their roles and responsibilities in supporting students and recognized the importance of their own personal attributes. The participants reported a number of challenges, particularly time, competing demands and paperwork, and suggested that a team approach and support groups could help to overcome these. The support for students provided by peers and health‐care assistants was recognized, as was the need to ensure that students are prepared to take responsibility for their learning.